From the onoma, reflection between Heraclitus and Plato - Cuartas, Juan Manuel (Estudios de Filosofía, 1996)
The ancient and fundamental reflection about the concept of noun has the double compromise of approaching both myth and logus. Plato's philosophical assumption about the concept of noun will be confronted wíth those of Heraclitus in serch of transparency and conventionality between nouns and things. First, Heraclitu's darkness does not marginalize the treatment of noun as the oracle which hides and reveals at the same time. Second, socratic dialectic denies but it also concedes the naturalness and the arbitrariness of the noun, this single-real instrument for naming and distinguishing. In this paper I take up this proposals, giving reasons to incorporare semantic features associated with nouns over and above their referent in any (genuine) semantic account of natural language.